2004
DOI: 10.1128/jvi.78.18.10166-10177.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Increase in Permeability of Nuclear Envelope upon Poliovirus Infection and Accompanying Alterations of Nuclear Pores

Abstract: Poliovirus and some other picornaviruses trigger relocation of certain nuclear proteins into the cytoplasm. Here, by using a protein changing its fluorescence color with time and containing a nuclear localization signal (NLS), we demonstrate that the poliovirus-triggered relocation is largely due to the exit of presynthesized nuclear protein into the cytoplasm. The leakiness of the nuclear envelope was also documented by the inability of nuclei from digitonin-permeabilized, virus-infected (but not mock-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
148
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(154 citation statements)
references
References 84 publications
6
148
0
Order By: Relevance
“…Both glucocorticoids (41) and mineralocorticiods (42) rapidly and transiently increase the permeability of the nuclear pore to dextrans in the 10 -20-kDa size range. This action precedes the initiation of gene transcription that is induced by these steroid hormones and thus may play a role in mediating that effect (40,41). Here we found that vasopressin, angiotensin, phenylephrine, and ATP each increase nuclear permeability.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Both glucocorticoids (41) and mineralocorticiods (42) rapidly and transiently increase the permeability of the nuclear pore to dextrans in the 10 -20-kDa size range. This action precedes the initiation of gene transcription that is induced by these steroid hormones and thus may play a role in mediating that effect (40,41). Here we found that vasopressin, angiotensin, phenylephrine, and ATP each increase nuclear permeability.…”
Section: Discussionsupporting
confidence: 49%
“…of GFP into the nucleus is increased in infected cells, and cells also lose the ability to retain NLS-tagged GFP within the nucleus (40). Both glucocorticoids (41) and mineralocorticiods (42) rapidly and transiently increase the permeability of the nuclear pore to dextrans in the 10 -20-kDa size range.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of several nuclear-cytoplasmic pathways has been documented during viral infection and an increase in nuclear permeability is a general strategy adopted by several viruses such as poliovirus, 19,45 rhinovirus 46 and cardiovirus 47 to gain access to the cell genetic information. In this case, the increased redistribution of NLS and NES-containing EGFP has been attributed to a perturbation of the docking of receptor-cargo complexes to the NPC.…”
Section: Discussionmentioning
confidence: 99%
“…These NPC extensions might function as initial cargo-docking sites during nuclear-cytoplasmic transport (Cullen, 2003;Kohler and Hurt, 2007). Some viruses severely damage NPC architecture, which leads to the inhibition of protein trafficking between the nucleus and the cytoplasm (Belov et al, 2004;Gustin and Sarnow, 2001;Gustin and Sarnow, 2002;Park et al, 2008;Porter and Palmenberg, 2009), inhibition of RNA export from the nucleus (Her et al, 1997;Satterly et al, 2007), and, in some instance, an increase of the nuclear membrane permeability at later times post-infection (Belov et al, 2004;Lidsky et al, 2006). Here, we report that PV 2A pro induces alterations in the NPC, which inhibits nuclear export of U snRNA, rRNA and mRNA but not that of tRNAs.…”
Section: Introductionmentioning
confidence: 99%